2013
DOI: 10.1111/echo.12282
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Echo Contrast at a Large Inter‐Atrial Septal Aneurysm

Abstract: Mini‐Abstract A 75‐year‐old woman presented with typical atrial flutter. Prior to ablation, a transesophageal echocardiogram demonstrated significant spontaneous echo contrast (SEC) at the site of a large inter‐Atrial septal aneurysm (ASA). After ablation of the arrhythmia, recovery of her left ventricular function, and 3 months of therapeutic anticoagulation with warfarin, she continued to have significant SEC at the site of her ASA, implicating the ASA as the source for the SEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It has been shown that a PFO increases the risk of cerebrovascular events (e.g. cryptogenic stroke) when associated with an ASA medical management of cerebrovascular and embolic events can be achieved primarily through the use of anticoagulation therapy in select cases . If the ASA is not associated with symptoms, then no surgical intervention is taken due to the low risk for cerebrovascular or embolic events .…”
Section: Subtypes Of Pseudotumorsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that a PFO increases the risk of cerebrovascular events (e.g. cryptogenic stroke) when associated with an ASA medical management of cerebrovascular and embolic events can be achieved primarily through the use of anticoagulation therapy in select cases . If the ASA is not associated with symptoms, then no surgical intervention is taken due to the low risk for cerebrovascular or embolic events .…”
Section: Subtypes Of Pseudotumorsmentioning
confidence: 99%
“…If the ASA is not associated with symptoms, then no surgical intervention is taken due to the low risk for cerebrovascular or embolic events . If an ASA results in symptoms and/or the patient is deemed to be at a higher risk for embolic events, such as in the presence of an associated PFO, then transcatheter or even surgical intervention in rare cases may need to be performed . It should be noted, however, that closure of PFO when associated with an ASA can be performed, but is still somewhat controversial …”
Section: Subtypes Of Pseudotumorsmentioning
confidence: 99%
See 2 more Smart Citations